Hourly Variation in the Flow Measurements in the Jesus Maria Watershed with the Cup-type Current Meter Method - Bonilla Valverde, José Pablo (2017)
Conducting punctual gauging measurements in Costa Rica constitutes a common practice for the evaluation of water resources for drinking water supply.  The country has a database composed of punctual measurements made in most of the rivers of Costa Rica with almost forty years of information. Within this database, a single data (punctual gauging) is used to characterize the whole month in which it was gauged. In order to corroborate the validity of this characterization, punctual gauging was performed every hour to confirm that the hourly variation is minimal.  The hourly gauging was carried out during the flow measurement campaign in the Jesus Maria watershed conducted on April 9th and 10th, 2013.  The flow measurements were performed using cup-type current meter method according to the ISO 2537: 2007 standard.  One third of the measurements showed less than ±1% variation and more than three quarters were in the range of ±5% variation. In all cases, excluding the lower basin of the Jesus Maria River, variations in the measurements are less than 10% relative to the median.  It is concluded that the hour variation is relatively small, and therefore, the database is validated – for the months at the end of the dry season.  This experience should be repeated in the same basin at other times of the year and on other basins to ensure that the temporal variability do not represent large differences in the flow.